Analisis Perkembangan Kognitif Teori Jean Piaget terhadap Anak Usia 4-12 Tahun pada Pembelajaran Matematika - Kasmawati, Kasmawati; Tahmir, Suradi; Danial , Danial (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to identify challenges in understanding abstract concepts caused by teaching methods that are not aligned with cognitive stages, such as imposing symbols without real objects, while integrating theory with global and national curricula, particularly in Indonesia. This research uses secondary literature analysis from reliable sources to uncover qualitative patterns of difficulties and practical recommendations, including practical applications, critiques of the universal stage sequence, and the integration of alternative approaches for inclusive learning. It also suggests educators adapt active strategies such as exploration and play to increase motivation, understanding, and mitigate problems related to individual variation and environmental factors. The findings yielded 10 research journal articles discussing the cognitive development of Jean Piaget's theory in children aged 4-12 years in mathematics learning. In conclusion, this theory plays a crucial role in improving the effectiveness of learning for children aged 7-12 years, particularly at the concrete operational stage, where students are able to think logically about real objects. Different cognitive development at each age affects children's ability to understand mathematical concepts such as basic operations, conservation, and problem-solving. Therefore, learning needs to be adapted through active, student-centered methods, such as discovery, cooperation, and inquiry.   Keywords: Mathematics, Jean Piaget's Theory.